Heat production of sedimentary rocks in Chengdao-Kendong area, Bohai Bay basin - Xiaolin Liu; Anyu Jing; Yuanjin Sun; Chao Sun; Ruibo Jiang; Xing Mu; Xiaoxue Jiang; Fang Xie; Yaodong Xu; Chuanqing Zhu (Unconventional Resources, 2025)
Sedimentary heat flow, as part of terrestrial heat flow, plays a key role in hydrocarbon generation by affecting the temperature of source rocks, thus influencing the thermal evolution and maturity of organic matter. The radioactive heat production rate of rocks is essential for studying sedimentary heat flow. Based on empirical formulas proposed by previous researchers that relate natural gamma log to heat production rates, this study calculated 26,707 rock heat production rate data points from 60 wells in the Chengdao-Kendong area. Results show that the average heat production rate of the sedimentary layers is 1.06 ± 0.34 μW/m3,and the different lithologies are as follows: mudstone 1.28 μW/m3, sandstone 1.05 μW/m3, conglomerate 1.01 μW/m3, glutenite 0.93 μW/m3, limestone 0.44 μW/m3, dolomite 0.45 μW/m3.The radioactive heat production ranges from 3.0 to 6.8 mW/m2. In the Changdi and Gudong areas, sedimentary layers contribute 6.3–10 % of the terrestrial heat flow, while the Kendong area's contribution is around 4.3 %. Moreover, the distribution of terrestrial heat flow is closely related to variations in basement depth, mainly influenced by mantle heat flow in the Chengdao-Kendong area.